Martín Lutero: Carta sobre el arte de traducir (1530) Sobre la traducción, la hermenéutica bíblica y la opción dogmática de la Reforma - Pena-Búa, Pilar (Teología y vida, 2021)
The Open Letter on Translating has been considered a classic of translation studies. Some say that, in it, Luther presented in a new and original way a method to interpret biblical texts and analyze the translator's work. However, our reading suggests that the primary reason of the Letter is not philological but theological, motivated by a precise theological and political context: the Augsburg Confession. This paper aims to: (I) analyze Luther's contribution to biblical translation studies. Then, (II) the hermeneutics applied by the reformer to the biblical texts, (III) determined by his dogmatic option on justification by faith, (IV) an option that underlies the content of the Letter. (V) We conclude with an analysis of the abilities and merits of Luther as a writer and translator.